2015
DOI: 10.1007/s13762-015-0845-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of electrocoagulation-treated spent wash sludge in making building blocks

Abstract: Minimization, utilization and disposal of industrial waste are very important from the environmental esthetic point of view. Sludge generated during the treatment of distillery spent wash by electrocoagulation process is highly complex in nature and requires proper disposal. In this context, the present study was conducted to employ the electrocoagulation-generated sludge as a partial replacement of cement while manufacturing the non-constructional building blocks. Various physiochemical and thermo-gravimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The decrease rate of sludge mass could be estimated through Equation (10). Therefore, the increase rate of the scum could be predicted by Equation (11).…”
Section: Routementioning
confidence: 99%
See 2 more Smart Citations
“…The decrease rate of sludge mass could be estimated through Equation (10). Therefore, the increase rate of the scum could be predicted by Equation (11).…”
Section: Routementioning
confidence: 99%
“…These results were in line with some studies [26,27] where the solution pH usually increases during the EC process. Kobya et al [26] reported that the final pH is always higher than the initial pH (3,5,7,9,11) in EC using iron electrode in treating textile wastewaters. Meanwhile, Kim et al [27] also came to the same conclusion-they found that the solution pH increased at the end of the process with initial pHs of 3, 5, 7 and 9 in the EC when treating the groundwater.…”
Section: Routementioning
confidence: 99%
See 1 more Smart Citation
“…The possible uses of EC sludge have not yet been widely explored, and only a few studies on sludge utilization or valorization in certain fields have been conducted. While a few studies on the use of sludge as fertilizers, pigments, construction materials, absorbents, and catalysts [9,[21][22][23] Resources 2021, 10, 127 2 of 15 and a few studies on EC sludge valorization have been reported, to our best knowledge, no practical reviews on this subject have been published. Thus, this review focuses on the EC sludge valorization studies that were published between 2010 and 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [17] investigated the application of sludge which were prepared by the electric flocculation of industrial printing and dyeing wastewater in anode materials in Li‐ion batteries. Sharma et al [18] utilized the electrocoagulation‐generated sludge as a partial replacement of cement to manufacture the non‐constructional building blocks. Zheng et al [19] developed a method for effective utilization of electric flocculation sludge, in the study, the sludge from the treatment of source‐separated urine was used to prepare iron phosphate.…”
Section: Introductionmentioning
confidence: 99%